Unplanned pregnancy-risks and use of emergency contraception: a survey of two Nigerian Universities - Ajayi, Anthony Idowu (BMC Health Serv Res, 2017)
BACKGROUND: The vulnerabilities of young women of low socio-economic status and those with little or no formal education tend to dominate the discourse on unplanned pregnancy, unsafe abortion and emergency contraception (EC) in sub-Saharan Africa. This article draws on a survey conducted among female undergraduate students to shed light on sexual behaviour and the dynamics of emergency contraceptive use among this cohort. METHODS: The survey involved 420 female undergraduate students drawn using a multistage sampling technique, while a self-administered questionnaire was used for data collection. Univariate and bivariate analyses were applied to examine the factors associated with the use of emergency contraception. RESULTS: Of the 176 female students who reported being sexually active in the year preceding the survey, only 38.6% reported the use of condom during the entire year. Of those who reported unplanned pregnancy anxiety n = 94, about 30.1% used EC, 20.4% used non-EC pills as EC, while others reported having used no EC. A few respondents (n = 3) had terminated a pregnancy under unsafe conditions. Awareness of EC (p < 0.001), knowledge of timing of EC (p = 0.001), perceived risk of unplanned pregnancy (p < 0.001), and level of study (p = 0.013), were significantly correlated with the use of EC. CONCLUSION: The study revealed that educated youths engaged in high-risk sexual activities and also, sought recourse to unproven and unsafe contraceptive methods. Poor knowledge of EC methods and timing of use, as well as wrong perception about EC side effects, are barriers to the utilisation of EC for the prevention of unplanned pregnancy among the study participants.